(untitled) (Research, Society and Development, 2020)
Telemonitoring is a secure technology that consists of telephone calls with the objective of stimulating, accompanying and supporting people with health needs, remote monitoring and continuous learning. Objectives: to analyze participants’ knowledge and expectations regarding diabetes and their health; discuss the repercussions of telemonitoring for the self-care of this specific group. Method: This is a qualitative research, with a participatory approach, developed in 2018, at the outpatient clinic of the Polyclinic Piquet Carneiro, from the State University of Rio de Janeiro, with 14 participants. The production of data was through the Talking Map, Telemonitoring and Interview.Results: Three categories emerged: Knowledge, expectations and health wishes; Telemonitoring technology from the perspective of the participants; The impact of telemonitoring on self-care. Conclusion: Telemonitoring in nursing is a viable technology, it allows a closer relationship, availability for distance monitoring, clarification of doubts, awareness for self-care and good health practices. This technology allowed to support and strengthen self-care practices for people with DM2, empowering them about healthy behaviors